Molecular mechanisms underlying resting-state brain functional correlates of behavioral inhibition - Shunshun Cui; Ping Jiang; Yan Cheng; Huanhuan Cai; Jiajia Zhu; Yongqiang Yu (NeuroImage, 2023)
Previous literature has established the presence of sex differences in behavioral inhibition as well as its neural substrates and related disease risk. However, there is limited evidence that speaks directly to the question of whether or not there are sex-dependent associations between behavioral inhibition and resting-state brain function and, if so, how they are modulated by the underlying molecular mechanisms. We computed functional connectivity density (FCD) using resting-state functional MRI data to examine their associations with behavioral inhibition ability measured using a Go/No-Go task across a large cohort of 510 healthy young adults. Then, we examined the spatial relationships of the FCD correlates of behavioral inhibition with gene expression and neurotransmitter atlases to explore their potential genetic architecture and neurochemical basis. A significant negative correlation between behavioral inhibition and FCD in the left superior parietal lobule was found in females but not males. Further spatial correlation analyses demonstrated that the identified neural correlates of behavioral inhibition were associated with expression of gene categories predominantly implicating essential components of the cerebral cortex (glial cell, neuron, axon, dendrite, and synapse) and ion channel activity, as well as were linked to the serotonergic system. Our findings may not only yield important insights into the molecular mechanisms underlying the female-specific neural substrates of behavioral inhibition, but also provide a critical context for understanding how biological sex might contribute to variation in behavioral inhibition and its related disease risk.